قياس جودة الخدمات التي تقدمها شركة موبايلي وأثر ذلك على رضا ضيوف الرحمن - العصيمي، صالح متروك حامد (المركز القومي للبحوث غزة, 2024)
هدفت الدراسة التعرف على أثر جودة الخدمات المقدمة من شركة موبايلي على رضا ضيوف الرحمن. تم استخدام المنهج الوصفي التحليلي، وكانت أدوات الدراسة الاستبانة كأداة لجمع البيانات والمعلومات، تكون مجتمع الدراسة من ضيوف الرحمن، وتم اختيار عينة عشوائية بسيطة، حيث بلغت 120 فردا من ضيوف الرحمن. وتوصلت نتائج الدراسة إلى أن الخدمات المقدمة من شركة موبايلي لضيوف الرحمن بلغ المتوسط الحسابي لها 3.97. وهذا يعني أن الوزن النسبي 79.34 %، ويدل ذلك على أن هناك قبولا من قبل أفراد العينة على مقياس جودة الخدمات المقدمة من شركة موبايلي لضيوف الرحمن بشكل عام. وجود علاقة ارتباطية دالة إحصائيًا بين جودة الخدمات التي تقدمها شركة موبايلي ورضا ضيوف الرحمن. إن المتغيرات المستقلة المؤثرة في رضا ضيوف الرحمن هي (الاستجابة، الأمان، التعاطف)، وعدم وجود تأثير لباقي المتغيرات. وأوصت الدراسة بضرورة قيام الشركة بعمل تقييمات مستمرة لضيوف الرحمن؛ للتأكد من أن الخدمة المقدمة خدمة مثالية. إجراء دراسة مقارنة بين شركة موبايلي وشركات أخرى منافسة؛ للتأكد من جودة الخدمات المقدمة ومستوى رضا الزبائن، لتحقيق ميزة تنافسية مستدامة بين الشركات الاهتمام بما يقدمه الزبائن من اقتراحات إلى جانب العمل على حل مشاكلهم، والاهتمام بالخدمات التي يرغبون بها، والعمل بها بجد. The study aimed to identify the impact of the quality of services provided by Mobily on the satisfaction of the pilgrims. The descriptive and analytical approach was used. The study tools were the questionnaire as a tool for collecting data and information, the study population consisted of the guests of Rahman, and a simple random sample was selected, amounting to 120 individuals from the guests of Rahman. The results of the study found that the services provided by Mobily to the pilgrims reached an arithmetic average of 3.97, which means that the relative weight is 79.34%, and this indicates that there is acceptance by the sample members on the scale of the quality of services provided by Mobily to the pilgrims in general. The existence of a statistically significant correlation between the quality of services provided by Mobily and the satisfaction of the pilgrims. The independent variables affecting the satisfaction of the pilgrims are (response, safety, empathy), and there is no effect of the rest of the variables. The study recommended that the company should conduct continuous evaluations of the pilgrims to ensure that the service provided is an ideal service. Conducting a comparative study between Mobily and other competing companies to ensure the quality of services provided and the level of customer satisfaction, to achieve a sustainable competitive advantage between companies. Paying attention to the suggestions provided by customers, as well as working to solve their problems and paying attention to the services they desire, and working hard.
Keywords: خدمات الاتصالات -- الميزة التنافسية -- رضا العملاء -- شركات الاتصالات -- السعودية